Incorporación de las TIC’S y su influencia en la enseñanza-aprendizaje del idioma inglés de séptimo año de la Unidad Educativa “Velasco Ibarra” periodo 2020 - Ramírez Allauca, Magaly del Rocío (2021)
This present research project was applied in the English area, through the incorporation of ICTs and its influence on the teaching-learning of the English language in the seventh year of the Velasco Ibarra Educational Unit, located in the Guamote canton, Chimborazo province, analyzing the methods and processes used for the incorporation of new technologies in the English language, and identifying the difficulties and strengths that the use of ICTs as a pedagogical resource can generate, for which an innovative, creative and dynamic Website was designed and implemented using the different techniques, and selecting the appropriate contents, so that the students apply in an interactive environment, allowing them to improve the academic level and develop language skills. Methodologically, the present work has a Quantitative approach, the methods used were hypothetical deductive, descriptive, correlational level, applied type, Pre-experimental design. The population was 60 students, where a sample of 22 students who are in the seventh year of EGB of the "Velasco Ibarra" Educational Unit was taken, so a survey was applied for the present study and get relevant information, and be able to determine the influence and incorporation of new ICT technologies have a significant impact on the development of the teaching and learning of the English language